2021
DOI: 10.1177/02761467211054354
|View full text |Cite
|
Sign up to set email alerts
|

The Other Pandemic: A Conceptual Framework and Future Research Directions of Junk Food Marketing to Children and Childhood Obesity

Abstract: During the last two decades, childhood obesity has become a global pandemic, creating harmful impacts on children, tutors, and society. If the obesity/overweight trend continues upwards, especially in developing countries, it may significantly alter millions of children's professional, social, and psychological well-being. Furthermore, it is conceivable that when obesity/overweight issues appear at a young age, they may persist during adulthood and disrupt individual development and community well-being. By ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…The difference between scoping reviews and systematic reviews is considerable. Researchers who perform systematic reviews first learn more about the amount of scientific literature on a certain issue (Centobelli et al, 2020;Ertz and Le Bouhart, 2022;; in our instance, this was done to learn more about prior research on both inclusive and qualitative ECEC approaches for achieving SDG4.2 goals.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between scoping reviews and systematic reviews is considerable. Researchers who perform systematic reviews first learn more about the amount of scientific literature on a certain issue (Centobelli et al, 2020;Ertz and Le Bouhart, 2022;; in our instance, this was done to learn more about prior research on both inclusive and qualitative ECEC approaches for achieving SDG4.2 goals.…”
Section: Methodsmentioning
confidence: 99%
“…As a reflection of the severe influence of the COVID 19 pandemic on children, such as being exposed to marketing from unhealthy products more often and rising obesity and junk food consumption problems (Ertz & Le Bouhart, 2021), many issues have emerged in this literature recently. Inevitably, a future systematic review on children and marketing will dramatically reveal the effects of the COVID 19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Antúnez et al (2021) found that the COVID‐19 pandemic helped industries of ultra‐processed products quickly promote their goods, create positive associations with their brands, and improve their brand image through their digital strategies. As a reflection of the severe influence of the COVID 19 pandemic on children, such as being exposed to marketing from unhealthy products more often and rising obesity and junk food consumption problems (Ertz & Le Bouhart, 2021), many issues have emerged in this literature recently. Inevitably, a future systematic review on children and marketing will dramatically reveal the effects of the COVID 19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate results of such a regulation were predicted to depend on how HFSS advertising patterns change in response 9. Though less is known about the potential effects of an online ban, emerging evidence indicates that online marketing techniques (eg, use of social media influencers) may be particularly pervasive and persuasive 17–19…”
Section: Introductionmentioning
confidence: 99%